ANALYSIS OF GRAMMATICAL ASPECTS OF THE TALK SHOW SENTILAN SENTILUN EDITION “DPR LIBRARY FOR WHOM?” - Juni Mahsusi; Baiq Yulia Kurnia Wahidah (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Abstract This study aims to determine what grammatical aspects are used in the Sentilan Sentilun discourse